2017
DOI: 10.1111/edt.12353
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognostic factors that influence the success of tooth autotransplantation in children and adolescents

Abstract: Article:Kafourou, V, Tong, HJ, Day, P orcid.org/0000-0001-9711-9638 et al. Outcomes and prognostic factors that influence the success of tooth autotransplantation in children and adolescents. Dental Traumatology, 33 (5). pp. 393-399,' which has been published in final form at https://doi.org/10.1111/edt.12353. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving.eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Items deposited in Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 27 publications
(65 reference statements)
3
69
0
6
Order By: Relevance
“…The success rate is higher for teeth with incomplete root formation, and the presence of an open apex is considered one of the key factors for clinical success. In a paediatric population, a success rate of 85.4% (defined as teeth with favourable periodontal ligament healing) and a survival rate of 94.4% (defined as teeth still present in their transplanted position, with signs of replacement resorption) were observed over a mean observation period of 2.6 years; in addition, the authors found that both pulp and periodontal ligament healing were strongly related to the stage of root development. In a long‐term study of 370 autotransplanted teeth, with an observation time ranging from 1 to 13 years, the authors observed three unsuccessful cases, with an overall 5‐year survival rate of around 95%: for immature teeth with a root development stage between 0 and 4 according to Moorrees et al ,.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success rate is higher for teeth with incomplete root formation, and the presence of an open apex is considered one of the key factors for clinical success. In a paediatric population, a success rate of 85.4% (defined as teeth with favourable periodontal ligament healing) and a survival rate of 94.4% (defined as teeth still present in their transplanted position, with signs of replacement resorption) were observed over a mean observation period of 2.6 years; in addition, the authors found that both pulp and periodontal ligament healing were strongly related to the stage of root development. In a long‐term study of 370 autotransplanted teeth, with an observation time ranging from 1 to 13 years, the authors observed three unsuccessful cases, with an overall 5‐year survival rate of around 95%: for immature teeth with a root development stage between 0 and 4 according to Moorrees et al ,.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of autotransplantation, compared to prosthetic rehabilitation, are improved aesthetics, function and mastication; in addition, the alveolar bone volume is preserved, due to maintained proprioception and physiological stimulation of the periodontal ligament. On the other hand, autotransplantation can be followed by unfavourable outcomes, which include pulp necrosis and infection, replacement resorption and lack of root development of immature teeth. The success rate is higher for teeth with incomplete root formation, and the presence of an open apex is considered one of the key factors for clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…Kafourou et al [ 17 ] reported the results of autogenous dental transplant according to two concepts, success and survival (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Kafourou et al, the preservation of the periodontal ligament is the key factor in the prognosis of autotransplantation [ 17 ]. Whether or not an autotransplanted tooth requires splinting is a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, The low cost of ATT and the development of technology in periodontal tissue regeneration lead it to become a potential treatment option to restore the occlusal function of lost tooth, meanwhile the transplanted tooth can function normally if it success [1] [2] [3]. However, in most reports about ATT, there are strict indications for the selection of cases, in which adequate alveolar bone is essential [4]. Some scholars tried to operate ATT when alveolar bone defect and got good results, but patients in these studies are adolescents whose teeth root are not formed completely and the maxillofacial developing will promote the alveolar bone and the teeth healing.…”
Section: Introductionmentioning
confidence: 99%